Expanding the Donor Pool With the Use of Extended Criteria Donation After Circulatory Death Livers. Issue 8 (2nd July 2019) - Mihaylov, Plamen; Mangus, Richard; Ekser, Burcin; Cabrales, Arianna; Timsina, Lava; Fridell, Jonathan; Lacerda, Marco; Ghabril, Marwan; Nephew, Lauren; Chalasani, Naga; Kubal, Chandrashekhar A.
Abstract : Use of donation after circulatory death (DCD) donor livers for transplantation has remained cautious in the United States. The aim of this study was to demonstrate the expansion of a DCD liver transplantation (LT) program with the use of extended criteria donor (ECD) DCD livers. After institutional review board approval, 135 consecutive DCD LTs were retrospectively studied. ECD DCD livers were defined as those with 1 of the following factors: donor age >50 years, donor body mass index >35 kg/m 2, donor functional warm ischemia time >30 minutes, and donor liver macrosteatosis >30%. An optimization protocol was introduced in July 2011 to improve outcomes of DCD LT, which included thrombolytic donor flush and efforts to minimize ischemia times. The impact of this protocol on outcomes was evaluated in terms of graft loss, ischemic cholangiopathy (IC), and change in DCD LT volume. Of 135 consecutive DCD LTs, 62 were ECD DCDs. In total, 24 ECD DCD LTs were performed before (era 1) and 38 after the institution of optimization protocol (era 2), accounting for an increase in the use of ECD DCD livers from 39% to 52%. Overall outcomes of ECD DCD LT improved in era 2, with a significantly lower incidence of IC (5% versus 17% in era 1; P = 0.03) and better 1‐year graft survival (93% versus 75% in era 1; P = 0.07). Survival outcomes for ECD DCD LT in era 2 were comparable to matched deceased donor LT. With the expansion of the DCD donor pool, the number of DCD LTs performed at our center gradually increased in era 2 to account for >20% of the center's LT volume. In conclusion, with the optimization of perioperative conditions, ECD DCD livers can be successfully transplanted to expand the donor pool for LT.